2021
DOI: 10.1088/1742-6596/2139/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Wear analysis in cutting tools by the technique of image processing with the application of two-dimensional matrices

Abstract: The useful life of the tools is a very important economic factor in the metal industry, so any improvement of the tool or material that can extend the useful life of the tools is productive. Tool deterioration can cause damage, cracking and vibration to the tool, and even damage to the machine. Effective tool wear control is most important. Effective tool wear control is most important. At present, there are some tools that can obtain the necessary conditions through digital image processing, and study their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Subsequently, based on this, a relationship between the number of pixels and the measurement of an object can be obtained. Previous research has shown the effectiveness of thresholding for the segmentation of regions of interest (ROIs) [52][53][54]. For the proposed method, different experiments were performed to have a robust methodology to segment the grooves (lower and upper) in order to obtain the width measurement.…”
Section: Results Of Cutting Speed Variation Testsmentioning
confidence: 99%
“…Subsequently, based on this, a relationship between the number of pixels and the measurement of an object can be obtained. Previous research has shown the effectiveness of thresholding for the segmentation of regions of interest (ROIs) [52][53][54]. For the proposed method, different experiments were performed to have a robust methodology to segment the grooves (lower and upper) in order to obtain the width measurement.…”
Section: Results Of Cutting Speed Variation Testsmentioning
confidence: 99%